Wilson disease: 30-year data on epidemiology, clinical presentation, treatment modalities and disease outcomes from two tertiary Greek centers. Issue 12 (December 2020) - Tampaki, Maria; Gatselis, Nikolaos K.; Savvanis, Spyridon; Koullias, Emmanouil; Saitis, Asterios; Gabeta, Stella; Deutsch, Melanie; Manesis, Emmanouil; Dalekos, Georgios N.; Koskinas, John
Abstract : Objective: Wilson disease is a rare genetic disorder of copper metabolism with a wide range of clinical presentations. The aim of this study is to describe the 30-year clinical experience in the management of Wilson disease patients followed at two Greek referral centers. Methods: A retrospective chart review was performed to identify past and present Wilson disease patients diagnosed during the last 30 years. Results: Sixty-three patients were included. The median age of diagnosis was 19 (3–59) years, while nine (14%) patients were older than 40 years old. Clinical presentation included asymptomatic liver disease (57.1%), neurological disease (20.6%), overt liver disease (12.7%), acute liver failure (6.3%) and other (3.2%). Kayser–Fleischer rings were detected in 27/62 with a higher frequency in neurologic patients ( P < 0.001). Ceruloplasmin values were low in 55/63 with significantly lower values in patients with neurological disease ( P = 0.048) and in cirrhotic patients ( P = 0.017). Increased 24-hour urine copper was measured in 59/63 patients. D-penicillamine was administered in 56/63 patients (88.8%), followed by trientine (6/63, 9.5%), while one patient needed liver transplantation at baseline. At least one treatment switch was performed in 18 patients. By the end of follow-up, all non-cirrhotic patients (25/25) were stable, 3/23 (13%) cirrhotic developed decompensated liver disease, two developed HCC, three received a liver transplant and two died. Five out of 13 neurologic patients had persisting symptoms despite treatment. Conclusion: Wilson disease presents with a wide spectrum of clinical manifestations and should be investigated even in older patients, as early diagnosis, close follow-up and treatment monitoring usually provide favorable outcomes.